Antimicrobial resistance patterns in Salmonella enterica subsp. enterica and Escherichia coli isolated from bivalve molluscs and marine environment. (March 2021) - Giacometti, Federica; Pezzi, Annalisa; Galletti, Giorgio; Tamba, Marco; Merialdi, Giuseppe; Piva, Silvia; Serraino, Andrea; Rubini, Silva
Abstract: The current study presents data on the antimicrobial resistance (AMR) patterns of 102 S. enterica subsp. enterica (72 Salmonella ser. Typhimurium and 30 monophasic S . Typhimurium serovar) and 79 Escherichia coli (and their phylogenetic group determination) isolates from different species of bivalve molluscs and from the water samples collected from the sub-areas of a mollusc production area near Ferrara (Italy). These areas were classified as Long-line, Lupini, B-Out, B-in, and Sacca. A retrospective evaluation was performed to assess the spatial trends of the resistance patterns of Salmonella and E. coli and the temporal trend for Salmonella ; the role of molluscs as AMR indicators and the potential use of E. coli as a microorganism indicator of AMR occurrence in a seawater environment were also investigated. Overall, 81% of Salmonella spp. and 75% of E. coli isolates were resistant to, at least, one antimicrobial agent (AA) and 44% and 38% of the isolates were multidrug resistant (MDR), respectively. The resistance levels of Salmonella were influenced by the investigated serovars. Monophasic S . Typhimurium serovar showed the highest resistance value with 70% of MDR isolates, in contrast with only 33% in S . Typhimurium. In monophasic S . Typhimurium versus S . Typhimurium, twofold resistance levels were observed to streptomycin (97 versus 43%), ampicillin (80 versus 40%) and tetracyclines (67 versus 36%). Regarding the temporal trend for Salmonella, strains were resistant to, at least, one AA, but this resistance was significantly lower during the first years of this 17-year sampling; however, in parallel MDR isolates, the resistance increased from 23% to a maximum level of 57% during the 2008–2012 period. On assessing the spatial trends, the Sacca area was found to show the lowest number of Salmonella spp. and E. coli strains resistant to, at least, one AA and MDR. For E. coli, the most commonly observed resistance was towards ampicillin (56%), streptomycin (52%), sulphonamides (30%) and ceftiofur (24%). The great majority (65%) of E. coli isolates belonged to the commensal phylogroups A and B1, with B1 as the dominant one, whereas most MDR isolates belonged to phylogroup C. Molluscs may be an efficient tool for antimicrobial resistance monitoring, and E. coli could be used as a microorganism indicator of the occurrence of antimicrobial resistance in seawater environment. Highlights: Bivalve molluscs are confirmed as efficient tool for antimicrobial resistance monitoring. High multi-resistant levels were observed in Salmonella spp. and E. coli from molluscs and water. Resistance levels for Salmonella are influenced by the investigated serovars. Spatial trends of MDR Salmonella strains are observed.